2005
DOI: 10.1117/12.600193
|View full text |Cite
|
Sign up to set email alerts
|

Life prediction and life extension of composite specimens using acoustic emission technique

Abstract: This paper discusses a proof test procedure for estimating and extending the fatigue life of composite coupons. The estimates were based on the acoustic emission data collected during the described proof test procedure. A group of coupon specimens that included both undamaged as well as damaged ones were tested to verify the ability to estimate the fatigue durability. For majority of the specimens tested the fatigue life of the coupons is inversely proportional to the cumulative AE energy collected during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Although the class presumed to consist of matrix-crack-induced AE events bore no useful conclusions, classes representing interface debonding and fibre failure were correlated with 'consumed' fatigue life. Nkrumah et al (2005) used a static proof-loading to estimate remaining life after fatigue on a limited experimental data set. A more elaborate approach is encountered in the work of Caprino et al (2005), using specimens subjected to constant-amplitude (CA) loading at one particular stress level.…”
Section: Work On Ae-based Fatigue Damage Assessmentmentioning
confidence: 99%
“…Although the class presumed to consist of matrix-crack-induced AE events bore no useful conclusions, classes representing interface debonding and fibre failure were correlated with 'consumed' fatigue life. Nkrumah et al (2005) used a static proof-loading to estimate remaining life after fatigue on a limited experimental data set. A more elaborate approach is encountered in the work of Caprino et al (2005), using specimens subjected to constant-amplitude (CA) loading at one particular stress level.…”
Section: Work On Ae-based Fatigue Damage Assessmentmentioning
confidence: 99%
“…Mizutani [9] compared data with generated waveforms to find relation between Lamb wave properties and fracture modes. Nkrumah [10] found that total AE energy during the proof tests were a good indicator of fatigue life of impact damaged woven glass-epoxy composite specimens. Jacques [11] showed that bonded sensors can detect AE signals with high fidelity by comparing these signals with signals from a Laser interferometer.…”
Section: Introductionmentioning
confidence: 99%
“…These classes were shown to correspond to the three main failure mechanisms, each being dominant at a particular stage of fatigue life. Nkrumah et al [12] used a static proof-loading to estimate remaining life after fatigue. Nevertheless, developed procedures relied on limited experimental data sets and no robust, validated predictive models were proposed.…”
Section: Introductionmentioning
confidence: 99%